If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3y + 4) + -1(-2y + -8) = 0 Reorder the terms: -1(4 + 3y) + -1(-2y + -8) = 0 (4 * -1 + 3y * -1) + -1(-2y + -8) = 0 (-4 + -3y) + -1(-2y + -8) = 0 Reorder the terms: -4 + -3y + -1(-8 + -2y) = 0 -4 + -3y + (-8 * -1 + -2y * -1) = 0 -4 + -3y + (8 + 2y) = 0 Reorder the terms: -4 + 8 + -3y + 2y = 0 Combine like terms: -4 + 8 = 4 4 + -3y + 2y = 0 Combine like terms: -3y + 2y = -1y 4 + -1y = 0 Solving 4 + -1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1y = 0 + -4 -1y = 0 + -4 Combine like terms: 0 + -4 = -4 -1y = -4 Divide each side by '-1'. y = 4 Simplifying y = 4
| 2(x-5)=12 | | 3(z+4)=2z+6 | | 1-3n=22 | | 28x^2-9x=0 | | (x+2)3=x-4 | | 6x-14=4x | | 500b-4b^4=0 | | 46-x=-3 | | 16x^3-44x^2+42x=0 | | 5(n-6)-(2-7n)=11n | | 4x-24=-92 | | 15+x=10+5x | | 4x^2-4x-120=0 | | 7x+6=9x+10 | | 12x^2-47x+40=0 | | 5t+2=16-2t | | 4-3v=16 | | x^2+0.3x+0.2=0 | | x^2-10x-75=0 | | 8x-2y=18 | | -24=3(y-7) | | -7x^4-25=0 | | 3x+.2x=2.5+3.5 | | 16x^2-19x=0 | | 13q=-39 | | 5(2+9)= | | x^3+3x^2=81x+243 | | -8x^4-10x^3=0 | | 2[w+3(w-1)]=18 | | -47-7x=-159 | | 2x+7-3x=3(9x+1)+4 | | 4y=-8x+12 |